2019
DOI: 10.1016/j.jadohealth.2019.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents' E-Cigarette Use: Increases in Frequency, Dependence, and Nicotine Exposure Over 12 Months

Abstract: This study examined changes in e-cigarette and dual-use frequency, levels of nicotine exposure and e-cigarette dependence, and device and e-liquid preferences over 12 months. Methods: Adolescents (N ¼ 173, aged 13e18 years) who reported past-month e-cigarette use and at least 10 lifetime uses were recruited from the San Francisco Bay Area. The sample was 75.1% male, 54.9% non-Hispanic White, mean age 16.6 years (standard deviation ¼ 1.2); 26.6% reported past-month cigarette smoking at baseline (i.e., dual use)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 31 publications
3
47
0
1
Order By: Relevance
“…4 Further, recent longitudinal research raises concern that use of e-cigarettes in adolescence can progress over time into sustained, frequent, dependent use. 5 An understanding of factors that influence adolescents' e-cigarette use is needed.…”
Section: Accepted Manuscript Introductionmentioning
confidence: 99%
“…4 Further, recent longitudinal research raises concern that use of e-cigarettes in adolescence can progress over time into sustained, frequent, dependent use. 5 An understanding of factors that influence adolescents' e-cigarette use is needed.…”
Section: Accepted Manuscript Introductionmentioning
confidence: 99%
“…Olfson et al (2019) [56] reported that e-cigarette users were 2.3 times more likely to be daily cigarette smokers than non-e-cigarette users, and 3.6 times more likely to report a tobacco use disorder. Recent longitudinal findings concur that dual use (cigarettes and e-cigarettes) was associated with an increase in e-cigarette frequency, nicotine exposure and ND in adolescent e-cigarette users with minimal cessation benefits [58]. In addition to the nicotine content of e-cigarettes, the "nicotine environment" of e-cigarette users likely represents an important barrier to cessation [37] and contributes to continued smoking and ND.…”
Section: Discussionmentioning
confidence: 85%
“…Eine weitere Studie rekrutierte 173 E-Zigarettennutzer im Alter von 13 -18 Jahren und verfolgte sie über ein Jahr. Auch für diese Kohorte zeigte sich, dass der weitaus überwiegende Teil (80,3 %) E-Zigaretten auch ein Jahr später konsumierte und der gleichzeitige Gebrauch von E-Zigaretten und konventionellen Zigaretten von 14,5 % auf 29,8 % anstieg [19].…”
Section: Introductionunclassified